Reading Experiences on Exploring Personal Reading Histories of English Study Program Learners of University of Riau - Delfi, Syofia; Diah, Fangiana Safitri; Safriyanti, Maria (FKIP-Universitas Riau, 2019)
Learners have different historical reading experiences which can be analyzed from any perspectives. This study aimed to explore “the reading experiences of two successful English study program learners of the Faculty of Teacher Training and Education University of Riau in Extensive Reading course based on Exploring Personal Reading Histories”. The suitable design in answering the research question of this study is a Case Study of the two successful learners in Extensive Reading course. Based on the result of the analysis of this study, it was found that reading experiences of English study program learners of the Faculty of Teacher Training and Education University of Riau based on Exploring Personal Reading Histories is individual contexts (the facilities provided by parents and the involvement of teachers) reflecting on the process in becoming competent in each level. As a result, their experiences develop their interest to do activities of reading without instruction. It also indicates that this study contributes to reading theory, especially extensive reading relating with the other theories as well as pedagogy in teaching and learning Extensive Reading by implementing Exploring Personal Reading Histories at the beginning of the course. This finding contributes to theory of reading, especially extensive reading and to methodology in terms of the appropriate instruments and analysis for qualitative researches.